ACP-EU JPA calls for the external implications of rice reform to be acknowledged - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
The ACP-EU Joint Parliamentary Assembly meeting in Brazzaville adopted a...